Sosialisasi Sistem Informasi Pemantauan Kesehatan dan Status Gizi Ibu Hamil Cegah Stunting - Faizah Wardhina; Rina Gunarti; Dwidya Poernareksa (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
Stunting is the condition of a toddler having a height that is less when compared to age. Stunting occurs due to malnutrition, especially during the first 1000 days of life. One way to prevent stunting is to fulfill nutrition and health services to pregnant women. At the examination of pregnant women, all examination results are recorded in the Maternal and Child Health book and the register book for pregnant women manually. This manual recording system can result in a slow search for the health history of pregnant women. In addition, there is a possibility that the KIA book is left at home. The purpose of this service activity is to contribute to the stunting reduction acceleration program by socializing the information system for monitoring the health and nutritional status of pregnant women for stunting prevention. The method of service using socialization begins with the introduction of the information system created and the implementation of trials. The results of this service activity are that the information system is considered very easy to use and the program can be used at Posyandu so that it can be integrated with the Primary Health Care.